Ciphertext policy attribute-based encryption scheme supporting direct revocation - Xi-xi YAN; Hui MENG (Tongxin xuebao)
In order to support fine-grained attribute revocation in direct revocation mode an attribute-based encryption scheme with efficient revocation was proposed.The model of ABE supporting attribute revocation was given,and a con-crete scheme was constructed which was proven its security under the standard model.Compared to the existing related schemes,the size of ciphertext and private/secret key was reduced.In additional,the new scheme achieved fine-grained and immediate attribute revocation which is more suitable for the practical applications.